18.2k views
3 votes
Complete the table shown below. f(x) = 2x2 - 8x + 6 1 0 2 y 3 4. 6 X= y = Z ​

Complete the table shown below. f(x) = 2x2 - 8x + 6 1 0 2 y 3 4. 6 X= y = Z ​-example-1
User Salathe
by
5.0k points

2 Answers

3 votes

Answer:

6, -2, 0

Explanation:

User Kingz
by
5.6k points
3 votes

Answer:

x = 6, y = -2, z = 0

Explanation:

To find x, we have to plug 0 into f(x). Therefore, x = f(0) = 2 * 0² - 8 * 0 + 6 = 6. Similarly, to find y, we have to plug 2 into f(x) so y = f(2) = 2 * 2² - 8 * 2 + 6 = -2. Finally, z = f(3) = 2 * 3² - 8 * 3 + 6 = 0.

User Charzhard
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.